2018
DOI: 10.1186/s12944-018-0853-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in erythrocyte polyunsaturated fatty acids and plasma eicosanoids level in patients with asthma

Abstract: BackgroundTo investigate the changes of polyunsaturated fatty acids (PUFAs) and their downstream eicosanoids in patients with asthma, the levels of erythrocyte membrane lipids and plasma lipid metabolites were examined.MethodsErythrocyte membrane lipids were extracted and esterificated, and then fatty acid compositions were determined by gas chromatography. The concentrations of six eicosanoids of PGE2, TXA2, LTB4, PGE1, 6-k-PGF1α and PGF2α in plasma were measured by ELISA.ResultsThe results showed that the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…Contrary to our hypothesis there was no difference in O3I, subjects with asthma had a better fatty acid profile, with lower saturated fatty acids, higher monounsaturated and n-3 fatty acids and a lower n-6 PUFA to n-3 PUFA ratio. This is in contrast to the results of Zhou et al [38], who found that subjects in China with asthma had a fatty acid profile composed mostly of SFAs, while those without asthma contained more PUFAs. Similar to our study, supplement and dietary intake data were not available to determine whether these differences were reflective of different dietary or supplement patterns or an effect of asthma.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our hypothesis there was no difference in O3I, subjects with asthma had a better fatty acid profile, with lower saturated fatty acids, higher monounsaturated and n-3 fatty acids and a lower n-6 PUFA to n-3 PUFA ratio. This is in contrast to the results of Zhou et al [38], who found that subjects in China with asthma had a fatty acid profile composed mostly of SFAs, while those without asthma contained more PUFAs. Similar to our study, supplement and dietary intake data were not available to determine whether these differences were reflective of different dietary or supplement patterns or an effect of asthma.…”
Section: Discussioncontrasting
confidence: 99%
“…Oxylipins are important lipid mediators that are formed from polyunsaturated fatty acids (PUFAs) such as arachidonic acid (ARA), linoleic acid (LA), α-linolenic acid (ALA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) [1][2][3] in reactions catalyzed by cyclooxygenase (COX), lipoxygenase (LOX), and cytochrome P450 (CYP 450) enzymes, and non-enzymatic oxidation pathways [1,2]. Oxylipins are involved in various biological processes but, primarily, are important for the regulation of inflammation [4][5][6][7][8]. The direction of oxylipins influence on inflammation depends on their PUFA precursor, usually n-3 PUFA derived oxylipins are anti-inflammatory and pro-resolving [1], while n-6 PUFA metabolites can promote inflammation [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…The pathway by which n-6 PUFA affects glucose levels and diabetes risk is not well-characterized but it is commonly linked to high adiposity and circulating proinflammatory eicosanoids. Indeed, circulating levels of n-6 PUFA have been associated with an increased BMI across the lifespan [37, 38] and elevated levels of proinflammatory eicosanoids in unhealthy and healthy humans [39, 40]. Recently, two independent MR studies, one using the UK Biobank (13,982 T2D cases and 273,412 controls) and the other using both the Wellcome Trust Case Control Consortium and an Australian adult and adolescent cohort (22,669 T2D cases and 58,119 controls) confirmed a causative association between an elevated BMI and the risk of T2D, i.e., OR = 1.37 (95% CI 1.12–1.68) per kilogram/square meter increase or OR = 1.47 (95% CI 1.17–1.85) per 5-kg increase [41, 42].…”
Section: Discussionmentioning
confidence: 99%